Constructing the 'Climate Crisis': A Critical Discourse Analysis of Rhetorical Strategies in G20 Leaders' Speeches - Tias Bastian Saragih; Partohap Saut Raja Sihombing; Selviana Napitupulu (Yayasan Bayt Shufiya Nusantara, 2026)
The escalation of the global climate crisis has necessitated a rigorous examination of how political leaders linguistically construct environmental realities to legitimize policy decisions. Despite extensive research on environmental communication, there remains a paucity of comparative critical discourse studies examining the linguistic dichotomy between Global North and Global South leaders within high-stakes economic forums. This study analyzes the rhetorical strategies employed by G20 leaders during the 2024 Summit to uncover how language serves as a tool for ideological dominance and evasion of responsibility. Utilizing Norman Fairclough’s Three-Dimensional Model of Critical Discourse Analysis (CDA), this qualitative study examines transcripts of keynote addresses from four G20 leaders. The analysis focuses on textual features, discursive practices, and broader social implications. The findings reveal a distinct divergence: Global North leaders predominantly utilize nominalization and passive voice to obfuscate agency regarding historical emissions, whereas Global South leaders employ high-modality affective language to frame climate change as an immediate existential threat requiring reparations. The study concludes that the discourse of